Developments of 2 Inches Loop Pipelines for Paraffin Deposition Testing Facility Using Plant Design Management System (PDMS) - Azni Yusra, Ahmad Kasmiri (2013)
The main frontier of exploring the deepwater ocean bed is due to the risk of paraffin deposition to the pipe. Going further offshore, the risk is increases because of the increasing of the length of pipelines and decreasing of the temperature. Paraffin will start to deposit along the pipeline once there is temperature gradient between oil and pipeline. According to forecaster, the world will increasingly rely on offshore and deepwater exploration. Therefore, it can be seen that the percentage of deepwater oil production is increases year by year as the development of complementary technology is achieved. The main objectives of this study is to develop a multiphase testing loop for paraffin deposition testing by using Plant Design Management System (PDMS). The paraffin deposition testing loop consisting oil system, natural gas system, inclinable test section unit and glycol system. Therefore, it is hope that this research will be beneficial to the industry, society and environment.